The P. gingivalis Autocitrullinome Is Not a Target for ACPA in Early Rheumatoid Arthritis. (April 2020) - Muñoz-Atienza, E.; Flak, M.B.; Sirr, J.; Paramonov, N.A.; Aduse-Opoku, J.; Pitzalis, C.; Curtis, M.A.
Rheumatoid arthritis (RA), a chronic inflammatory disease affecting primarily the joints, is frequently characterized by the presence of autoimmune anticitrullinated protein antibodies (ACPA) during preclinical stages of disease and accumulation of hypercitrullinated proteins in arthritic joints. A strong association has been reported between RA and periodontal disease, and Porphyromonas gingivalis, a known driver of periodontitis, has been proposed as the microbial link underlying this association. We recently demonstrated P. gingivalis –mediated gut barrier breakdown and exacerbation of joint inflammation during inflammatory arthritis. In the present study, we investigated another potential role for P. gingivalis in RA etiopathogenesis, based on the generation of ACPA through the activity of a unique P. gingivalis peptidylarginine deiminase (PPAD) produced by this bacterium, which is capable of protein citrullination. Using a novel P. gingivalis W50 PPAD mutant strain, incapable of protein citrullination, and serum from disease-modifying antirheumatic drug–naïve early arthritis patients, we assessed whether autocitrullinated proteins in the P. gingivalis proteome serve as cross-activation targets in the initiation of ACPA production. We found no evidence for patient antibody activity specific to autocitrullinated P. gingivalis proteins. Moreover, deletion of PPAD did not prevent P. gingivalis –mediated intestinal barrier breakdown and exacerbation of disease during inflammatory arthritis in a murine model. Together, these findings suggest that the enzymatic activity of PPAD is not a major virulence mechanism during early stages of inflammatory arthritis.